4(2x-3) - 14 =-5 (3x - 4)how to verify
Answers
Answered by
3
Solution:
4(2x-3) - 14 =-5 (3x - 4)
=> 8x-12-14 = -15x+20
=> 8x-26 = -15x+20
=> 8x+15x = 20+26
=> 23x = 46
=> x = 46/23
=> x = 2
Verification :
Substitute x = 2 , in the equation, we get
LHS = 4(2x-3)-14
= 4(2*2-3)-14
= 4(4-3)-14
= 4×1-14
= 4 - 14
= -10 ---(1)
RHS = -5(3x-4)
= -5(3*2-4)
= -5(6-4)
= -5×2
= -10 ---(2)
Therefore ,
LHS = RHS
•••
Answered by
1
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d3a/5053ce43f8d7ea2d6d77135830d78852.jpg)
Similar questions